2019
DOI: 10.1111/irv.12664
|View full text |Cite
|
Sign up to set email alerts
|

How to assess the effectiveness of nasal influenza vaccines? Role and measurement of sIgA in mucosal secretions

Abstract: Secretory IgAs (sIgA) constitute the principal isotype of antibodies present in nasal and mucosal secretions. They are secreted by plasma cells adjacent to the mucosal epithelial cells, the site where infection occurs, and are the main humoral mediator of mucosal immunity. Mucosally delivered vaccines, such as live attenuated influenza vaccine (LAIV), are able to mimic natural infection without causing disease or virus transmission and mainly elicit a local immune response. The measurement of sIgA concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 85 publications
0
31
0
Order By: Relevance
“…Previous studies have shown that serum antibody levels are a poor measure of LAIV vaccine efficacy ( 50 ). In contrast, nasal mucosal secretory IgA, the predominant immunoglobulin produced in response to infection of the nasal mucosa, has been shown to be a much better indicator of LAIV-induced antibody responses (reviewed in Reference 45 ). We developed an anti–LAIV-IgA ELISA to determine the effects of cigarette smoking and e-cigarette use on antibody production and found that LAIV-specific IgA levels increased as expected in nonsmokers after LAIV inoculation but did not increase in e-cigarette users and cigarette smokers ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that serum antibody levels are a poor measure of LAIV vaccine efficacy ( 50 ). In contrast, nasal mucosal secretory IgA, the predominant immunoglobulin produced in response to infection of the nasal mucosa, has been shown to be a much better indicator of LAIV-induced antibody responses (reviewed in Reference 45 ). We developed an anti–LAIV-IgA ELISA to determine the effects of cigarette smoking and e-cigarette use on antibody production and found that LAIV-specific IgA levels increased as expected in nonsmokers after LAIV inoculation but did not increase in e-cigarette users and cigarette smokers ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that e-cigarette use is prevalent among teenagers who are recommended for complete immunization schedules, understanding whether and how vaping could modify vaccination-conferred immunity is an unexplored field. Secretory IgA is the principal antibody isotype present in nasal secretions ( 45 ) and neutralizes pathogens, like influenza, at the site of infection before they attach, enter, and replicate in the host cell ( 45 ). Although conventional intramuscularly administered influenza vaccines generate a serum IgG-antibody response, protection conferred by LAIV vaccination is believed to be derived by its ability to generate a robust and sustained nasal mucosal IgA response ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIgA antibodies have neutralization potential pathogens at the entrance site before they can attach to epithelial cells and overcome the epithelial surface. Considerable levels of Influenza virus specific SIgA was secreted in saliva, suggesting that saliva works as humoral immunity against influenza virus [ 20 , 21 ]. The development of mucosal vaccines that aim to induce influenza virus-specific IgA has been working on.…”
Section: The Influence Of Oral Health On Influenza Virus Infectionmentioning
confidence: 99%
“…74 In mucosae, technical difficulties in obtaining samples also exist, although standardized methods in our laboratory and by others are optimal. 3,4,75,76 Immunogenicity-the ability of an immunogen to elicit high titers of Abs and T cell proliferation or cytokine secretion-is just the first step on the long way to obtain an efficacious vaccine. 77 One side of the problem is that we still lack enough understanding of the types of immune responses that protect the host from specific pathogens.…”
Section: Correlates Of Protection Against Mucosal Pathogens Are Not Ementioning
confidence: 99%